1980
DOI: 10.1159/000176342
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Feeding Different Levels of Mustard Oil in Monkeys

Abstract: Three groups, each of 9 adult male monkeys were maintained for about 18 months on diets containing mustard oil, either 5 or 10%; or 10% peanut oil, respectively. Histological examination of hearts of monkeys fed either 5 or 10% mustard oil diets did not reveal any abnormality attributable to mustard oil intake, such as vacuolation and fibrosis of myocardium. However, the oxygen consumption, RCR and ADP/O ratio, were significantly lower in the mitochondria isolated from monkeys receiving 109í mustard oil than t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

1980
1980
1983
1983

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…In these studies on monkeys, the concentration of erucic acid in the myocardium was proportional to the level of mustard oil in the diet (10,11). The mean concentration of erucic acid in the myocardial fat of monkeys which had received 5 and 10% mustard oil were 9.5 and 14.4%, respectively, of the total fatty acids (10). In animals that received mustard oil at a 20% level, the concentration of erucic acid in the fat of hearts which showed fibrosis was 38% of total fatty acids and that in non-fibrotic hearts was 24% of the total fatty acids (11).…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…In these studies on monkeys, the concentration of erucic acid in the myocardium was proportional to the level of mustard oil in the diet (10,11). The mean concentration of erucic acid in the myocardial fat of monkeys which had received 5 and 10% mustard oil were 9.5 and 14.4%, respectively, of the total fatty acids (10). In animals that received mustard oil at a 20% level, the concentration of erucic acid in the fat of hearts which showed fibrosis was 38% of total fatty acids and that in non-fibrotic hearts was 24% of the total fatty acids (11).…”
Section: Discussionmentioning
confidence: 96%
“…Results of diet surveys carried out in several parts of Calcutta have shown that mustard oil provides between 1 and 3% of total daily calorie intake (6). Although monkeys fed a diet which contained 20% mustard oil developed myocardial fibrosis (5), those fed a diet which contained lower levels of either 5 or 10% mustard oil did not show fibrotic changes even after prolonged feeding (10), indicating that the level of mustard oil consumed was important in the development of myocardial fibrosis. In these studies on monkeys, the concentration of erucic acid in the myocardium was proportional to the level of mustard oil in the diet (10,11).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation